(untitled) (Journal of Advanced Veterinary and Animal Research, 2019)
Objective: The objective of this study was to investigate the impact of whey protein concentrate (WPC) derived from camel’s milk on cheese yield, some chemical, microbial, and organoleptic properties of low salt soft cheese during refrigerated storage. Materials and Methods: Cheeses made from buffalo’s milk without and with adding 4,000 and 8,000 μg/ml WPC. Results: Addition of WPC significantly increased the yield, titratable acidity, and decreased pH of the resultant cheese samples. Cheese treated with 8,000 μg/ml WPC had the highest effect on the reduction of the total bacterial count, coliform, molds, and yeast up to 29th day of storage in comparison to the 25th day and 17th day in cheese with 4,000 μg/ml and control samples, respectively. The organoleptic evaluation indicated that adding of WPC improved flavor, body, and texture and appearance of the cheese. Conclusion: The present study demonstrated that the application of camel’s WPC at 8,000 μg/ml in cheese can improve organoleptic and microbiological proprieties of low salt soft cheese and prolong its shelf-life at refrigerated storage up to 29 days in comparison to 25 days and 17 days in cheese treated with 4,000 μg/ml WPC and control cheeses, respectively. So, the present WPC has a potential for preservation as a food ingredient and natural food preservative. J. Adv. Vet. Anim. Res., 6(4): 528-535, December 2019